14.6k views
1 vote
If z=-1-sq root 3i and z^6=a+bi then a = ___ and b= ___

User Abhijit
by
5.3k points

1 Answer

2 votes

Answer:

a=64 and b=0

Explanation:


z=-1-√(3)i

use
z=e^(ix)=cosx+isinx

Now we find out x using given z


z=-1-√(3)i

Multiply and divide the right side by -2


z=-2((1)/(2) +(√(3))/(2))

We know cos(pi/3) = 1/2

sin(pi/3)= sqrt(3)/2


z=-2((1)/(2) +(√(3))/(2))


z=-2(cos((\pi)/(3))+sin((\pi)/(3))

compare the above equation with use
z=e^(ix)=cosx+isinx

x= pi/3

so
z=-2e^{(\pi)/(3)i}


z^6=64(e^{(\pi)/(3)i})^6


z^6=64e^{(6\pi)/(3)i}


z^6=64e^(2\pi*i)

Plug in 2pi in the z equation


z=64e^(2\pi*i)=64(cos(2\pi)+isin(2\pi))

So z= 64(1 + i(0))

z=64

So a= 64 and b=0


User Caroline Morris
by
5.5k points